Improving Upland Acid Soil Properties And Increasing Maize Yield By Phosphate Rock Application With Organic Acids. (21st November 2022) - Sutriadi, Mas Teddy; Anwar, Syaiful; Mulyanto, Budi; Darmawan,; Husnain,; Jaya, Adi
Abstract : Problems encountered in the management of upland acid soils, besides soil pH, are also low in phosphorus (P) content and less available to plants. The addition of organic acids (OAs) to the direct application of phosphate rock (PR) has not been widely studied yet and is expected to improve upland acid soil properties. The research aims to determine the effect of adding OAs on the direct application of PR to improve upland acid soil and increase maize yield. It was a greenhouse experiment using a randomized complete design in a factorial arrangement with three replications. The treatments consisted of four types of OA (citric, humic, succinic, and oxalic acid) and five OA concentration levels (0, 25, 50, 100, and 200 ppm). The hybrid maize ( Zea mays L) was used as the test crop. The parameters observed were soil properties (pH, exchangeable H (H + ), exchangeable Al (Al 3+ ), exchangeable Ca (Ca 2+ ), cation exchange capacity (CEC), available P (as P-Bray1)) and maize growth (plant heights and yield). The results show that the types of OA treatments had no significant effect on soil properties and maize yield; in contrast, the concentrations of OA levels were able to improve soil properties as indicated by a significant effect on pH, H +, Al 3+, Ca 2+, CEC, available P, and increased maize yield. An increase in soil pH due to the addition of OAs to the direct application of PR could increase Ca 2+ and CEC and decrease Al 3+ and H +, while increasing available P for plants. Although not significantly different, oxalic acid was able to improve the observed soil properties and maize yield, followed by citric, humic, and succinic acids. The maximum OA concentration was 126.9 ppm. We can say that the main finding of this research is that oxalic, citric, humic, and succinic acids at a concentration of 126 ppm can be applied to phosphate rock. In Indonesia, humic acid has been widely applied by farmers because it is easy to obtain. Therefore, it can be applied to phosphate rock.